2016
DOI: 10.1002/ldr.2597
|View full text |Cite
|
Sign up to set email alerts
|

Biochar from Pyrolysis of Deinking Paper Sludge and Its Use in the Remediation of Zn‐polluted Soils

Abstract: An increasing proportion of recycled fibres are used in paper industries. Removing the ink, clay, coatings and contaminants from paper waste in order to produce recycled fibres creates large amounts of deinking paper sludges. The preparation of biochar from pyrolysis of this waste and its use in soil remediation contaminated with heavy metals could be an interesting valorization alternative. Our aim was to study the influence of biochar from deinking paper sludge (HP) pyrolysis in the treatment of Zn‐polluted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…The higher content of carbonates in MSW‐derived biochar promoted increases in soil pH up to 5·5, and the addition of MaW did not contribute to further decrease metal mobility. Previous research has also reported that pH is the main driven factor controlling metal mobility with addition of amendments (Ahmad et al ., ; Rajapaksha et al , ; Paz‐Ferreiro et al ., ). Thus, the addition of warble waste as a source of CaCO 3 is confirmed as a sustainable material for the creation of Technosols from pyritic tailings to decrease metal toxicity, also observed in previous studies (Pardo et al , ; Zornoza et al , ).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The higher content of carbonates in MSW‐derived biochar promoted increases in soil pH up to 5·5, and the addition of MaW did not contribute to further decrease metal mobility. Previous research has also reported that pH is the main driven factor controlling metal mobility with addition of amendments (Ahmad et al ., ; Rajapaksha et al , ; Paz‐Ferreiro et al ., ). Thus, the addition of warble waste as a source of CaCO 3 is confirmed as a sustainable material for the creation of Technosols from pyritic tailings to decrease metal toxicity, also observed in previous studies (Pardo et al , ; Zornoza et al , ).…”
Section: Discussionsupporting
confidence: 79%
“…Addition of biochar was also directly involved in the immobilization of Cd and Zn by retention in its oxidizable fraction (organic compounds) (Figure ), a trend reported by previous authors (Adriano et al ., ; Harvey et al ., ; Mohamed et al ., ). This could be related to adsorption processes, because biochars, and mostly those prepared at high temperature, have a larger surface area, which can complex metals (Paz‐Ferreiro et al , ). Mohamed et al .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Although biochar application has shown some variable results, depending on soil type, biochar feedstock, biochar pyrolysis temperature, and other environmental factors; there are a number of potential positive aspects associated with the use of biochar as a soil amendment, including increased soil nutrient availability and uptake by plants (Sigua, Novak, Watts, Johnson, & Spokas, ; Zornoza, Moreno‐Barriga, Acosta, Muñoz, & Faz, ); enhanced organic and inorganic fertilizers use efficiency (Schulz & Glaser, ); increased soil mineral N (NH 4 and NO 3 ) retention (Clough, Condron, Kammann, & Müller, ); reduced nutrient losses and fertilizer demand (Ding et al, ); improved soil physical properties (soil water holding capacity, soil aeration, bulk density, porosity, aggregate stability, infiltration rate, and hydraulic conductivity; Atkinson, Fitzgerald, & Hipps, ; Mukherjee & Lal, ); increased base saturation and liming effect on acidic soils (Wang et al, ); stabilization of heavy metals and reduced bioavailability to plants growing in contaminated soils (Ahmad et al, ; Paz‐Ferreiro, Plasencia, Gascó, & Méndez, ); stimulation of microbial populations and functioning (Zhu, Chen, Zhu, & Xing, ); increased crop performance and productivity (Jeffery, Verheijen, van der Velde, & Bastos, ); enhanced symbiotic N fixation in legumes (Mia et al, ); reduced salinity, drought, and heat stresses impact on plant growth and soil properties (Ali et al, ; Drake, Cavagnaro, Cunningham, Jackson, & Patti, ; Fahad et al, ). In conjunction with chemical fertilizers, biochar improves the nutrient use efficiency of plants by enhancing soil nutrient retention for a longer period of time, and via the slow release of nutrients according to plant requirements (DeLuca, MacKenzie, & Gundale, ).…”
Section: Introductionmentioning
confidence: 99%